New Plants for Florida: Blueberry - Paul Lyrene; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
After several years and cycles of crossing and selection, Paul Lyrene developed today’s newer commercial varieties of blueberries, which have larger berries, stronger bushes and higher yields. These new berries also ripen earlier and are easier to pick and ship. Today’s varieties have made Florida blueberry production what it is today – a crop that sells 4 million pounds per year, with a farm-gate value of $20 million. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.